(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2015)
The present study made an attempt to look into the linguistic characteristics strongly related to the mother’s temperament vis-à-vis the success of the early communication with their infants. By comparing percentage data we can conclude that all of the mothers characterised along the scales unstable—stable and introvert–-extrovert do use motherese strategies, out of which scenarios given by affirmative intonation, the various communication functions and the verbal paradigm were analysed. We found that the stage and the frequency at which these language features were used varied significantly and strongly depended on the mother’s personality factors. We can therefore establish that mothers with different temperaments can be characterised by a different combination of language strategies facilitating first language acquisition. No mother temperament displayed a total lack of motherese elements.